Alpine Timberline Research Gap in Himalaya: A Literature Review - Dutta, Pijush Kumar; Dutta, B. K.; Das, A. K.; Sundriyal, R. C. (Indian Forester, 2014)
Alpine timberline, considered to be important ecotone supports rich and highly vulnerable biodiversity and represent one of the most distinct boundaries between forest to tree less alpine areas. It has attracted geographers and ecologist to do research for a long time on the phenomena it encompasses. In recent time, alpine treeline ecotones across most of the world’s mountains are being studied because of their potential for monitoring the effects of climate warming on forest ecosystem. Besides, alpine pasture areas in and around timberline zone and commercially important medicinal plants along timberline have also been playing important role as a source of livelihood of mountain communities settled in nearby area. In recent time, with the change in socio-economic aspiration of local mountain communities, there has been a rapid increase in pressure on natural resources in and around timberline area. However, compared to studies of timberline area of European Alps, Andes of South America and mountains of North America, which has reached a very advance stage, very limited studies on timberline of Himalayan mountain range have been carried out. In the present paper, review of timberline research work carried out in the mountain ranges of Europe, North America and Himalaya have been carried out to highlightthe gap in alpine timberline research work in Himalaya.